MANAGEMENT OF LOWER LIP MUCOCELE: A CASE REPORT - Syahrir, Syakriani; Wajdiyah, Ummi (Hasanuddin University, 2022)
Objective: This study reviews lower lip mucocele in children and its management. It also presents a case report of a 14-year-old-girl diagnosed with a lower lip mucocele.Method: Excision surgery was performed under local anesthesia, and mucocele was incised vertically so that separates the mucosa on it. The mucocele was resected from the base, suturing was made and removed on the 10th day.Result: On the sixth day had been removed suture, patient controlled. The scar appeared to have closed entirely and the hyperemic was not visible.Conclusion: Excision surgery is still an option treatment although considered a conservative way to remove the mucocele. This technique does not cause excessive bleeding with rapid wound healing. It does not require special equipment, is inexpensive, and can be performed by the dentist.